Hubungan Keluhan Iritasi Mata dengan Lama Kontak dan Kadar Klorin pada Air Kolam Renang Universitas Lampung - Fahma Azizaturrahmah; Rani Himayani; Anggraeni Janar Wulan (Medula, 2020)
Eye irritation is an inflammation of conjunctival layer caused by exposure of irritant substances such as chemicals. Chlorine in swimming pool water is one of the chemical substances that can cause eye irritation complaint at a certain level and time. This study aims to determine the relationship between eye irritation with contact time and swimming pool chlorine levels. The research design was quantitative with cross sectional method, with sampling technique of consecutive sampling. There were 96 participants. Chlorine levels were tested with chlorine meter then eye complaint and contact time were taken from the questionnaire filling. The analysis test was performed by using chi-square test. There was correlation between eye irritation with chlorine level with result of chi-square test p value = 0,002 and odds ratio equal to 4,577. There was correlation between eye complaint with chlorine contact time with chi-square test p value = 0,04 and odds ratio 2,857. Conclusion: Participants with chlorine exposure more than standard were at risk 4,577 times to have eye irritation than participants with chlorine exposure at standard. Participants with chlorine exposure more than 15 minutes were at risk 2,857 times to have eye irritation than participants with chlorine exposure less than 15 minutes.